Public Authorities & Their Procedures in Malaysia: 1977-1981 - Jain, M.P. (Journal of Malaysian and Comparative Law, 1984)
The modern state is an administrative state. With the demise of the laissez faire, the state has assumed a very activist role. The state is called upon to undertake varied activities and functions to promote the socio-economic welfare of the people. This leads to an expansion of administrative process in their country. To meet the various demands made on it, the state establishes, from time to time, new and diverse public authorities, and lays down new administrative procedures, because most of the newly developing acitivities cannot be performed effectively through the traditional government departmental structure.